2021
DOI: 10.1002/onco.13901
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Treatment with Angiogenesis-Inhibitor Dovitinib Prior to Local Therapy in Hepatocellular Carcinoma: A Phase II Study

Abstract: Background. Hepatocellular carcinoma (HCC) recurrence rates following locoregional treatment are high. As multireceptor tyrosine kinase inhibitors (TKI) targeting vascular endothelial growth factor receptors (VEGFR) are effective in advanced HCC, we assessed the efficacy and safety of neoadjuvant systemic treatment with dovitinib in early and intermediate stage HCC. Methods. Twenty-four modified Child-Pugh class A early and intermediate stage HCC patients received neoadjuvant oral dovitinib 500 mg daily (5 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…The primary target of dovitinib is VEGFR1–3, but it also targets FGFR1–3, PDGFRβ, FMS‐like tyrosine kinase 3 (FLT3), KIT, RET, TrkA, and colony stimulating factor 1 (Csf‐1). Dovitinib has shown therapeutic effects in breast cancer, HCC, prostate cancer, renal cell carcinoma, melanoma, multiple myeloma, and gastrointestinal mesenchymal tumors and its major drug‐related toxicities include nausea, vomiting, fatigue, anorexia, and diarrhea 333–335 . Lucitanib strongly inhibits FGFR1, FGFR2, and VEGFR1–3, and it has antiangiogenic and broad‐spectrum antitumor activity against several cancers, including small cell lung cancer, breast cancer, nasopharyngeal carcinoma, colorectal cancer, ovarian cancer, and kidney cancer 336,337 .…”
Section: Fgfr Acts As a Therapeutic Targetmentioning
confidence: 99%
“…The primary target of dovitinib is VEGFR1–3, but it also targets FGFR1–3, PDGFRβ, FMS‐like tyrosine kinase 3 (FLT3), KIT, RET, TrkA, and colony stimulating factor 1 (Csf‐1). Dovitinib has shown therapeutic effects in breast cancer, HCC, prostate cancer, renal cell carcinoma, melanoma, multiple myeloma, and gastrointestinal mesenchymal tumors and its major drug‐related toxicities include nausea, vomiting, fatigue, anorexia, and diarrhea 333–335 . Lucitanib strongly inhibits FGFR1, FGFR2, and VEGFR1–3, and it has antiangiogenic and broad‐spectrum antitumor activity against several cancers, including small cell lung cancer, breast cancer, nasopharyngeal carcinoma, colorectal cancer, ovarian cancer, and kidney cancer 336,337 .…”
Section: Fgfr Acts As a Therapeutic Targetmentioning
confidence: 99%
“…We read with interest the article published by Woei-A-Jin et al and commend the authors for bringing this interesting report to the field of neoadjuvant systemic treatment in early- and intermediate-stage hepatocellular carcinoma (HCC). 1 Currently, there is an urgent need for active systemic treatment as a preoperative strategy to achieve disease down-staging and expand the proportion of patients who may derive benefit from locoregional therapies. 2 Despite optimal local control, most of patients with HCC recur, and the 5-year survival rate for early- and intermediate-stage HCC ranges between 15% and 50%, with failure to control micro-metastatic disease severely influencing early relapse in this setting.…”
mentioning
confidence: 99%
“…In The Oncologist , Woei-A-Jin et al reported the results of a phase II trial including 24 patients with early- and intermediate-stage HCC, treated with neoadjuvant oral dovitinib for 4 weeks, followed by locoregional therapy. 1 Of note, the 48% of patients had an overall response, including 13% complete remission; however, tolerability has represented an important issue, with frequent dose reductions and interruptions. We believe some elements deserve discussion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We appreciate the letter by Rizzo et al, 1 in which they acknowledged the important pharmacodynamic information obtained from our neoadjuvant phase II study of dovitinib prior to local/locoregional therapy in early- and intermediate-stage hepatocellular carcinoma (HCC). 2 …”
mentioning
confidence: 99%